Resiliência em cadeias de suprimentos humanitárias - Nunes, Rodolfo Modrigais Strauss (2022)
Faced with a global scenario with increasing events of natural disasters and weather extremes, this thesis investigates which are the most relevant aspects in the formation of resilience of humanitarian supply chains (RHSC) with a focus on local services, aiming to develop a framework that explains the phenomenon. For this, the thesis was structured in the format of four articles. The first article (Chapter 2 of the thesis) consists of a literature review based on bibliometric mapping techniques, aiming to identify the intellectual structure of humanitarian operations, including supply chains and humanitarian logistics. As a main result, the intellectual structure of this field of study is visually presented, through the VOSviewer software, including the main researches and emerging themes, making it possible to confirm the opportunity for better development of the theme of resilience in humanitarian supply chains. In the second article (Chapter 3), we sought to explore patterns of structure, processes and flows of humanitarian service supply chains, as it was found that, although there are some models of analysis of service supply chains in the commercial context, there was still a lack studies focusing on service supply chains in the humanitarian context of coping with natural disasters. As a methodology, an exploratory research of mixed methods was chosen, through a set of interviews, observation, document analysis and computerized social network analysis. The results allowed the proposition of a specific analytical framework to better understand service supply chains in the humanitarian context of coping with natural disasters and the influence of their structure on resilience. The third article (Chapter 4) consists of a qualitative research to identify the main practices of humanitarian supply chains that deal with natural disasters, to understand how they contribute to the formation of resilience. For this, a multiple case study was developed in chains of five local civil defense agencies in Brazil, which work in a humanitarian context to preserve lives in the face of the threats of natural disasters. The results indicate that the implementation of replicable practices can contribute to the generation of resilience in humanitarian supply chains, improving their performance. Based on the theoretical lens of practice-based view, it was possible to map a transferable set of 29 practices and 13 capabilities that would build the resilience of humanitarian supply chains of services in the context of natural disasters. Finally, the fourth article (Chapter 5) investigates the relationships between resilience in humanitarian supply chains, environmental and climate contingencies and community resilience, in the context of natural disasters, through a mixed methods research with multiple case studies and big data techniques for analyzing unstructured data. In light of contingency theory, the results indicate that changes in contingency variables can lead to an increase in disaster risk, requiring adjustments or adaptations in the level of resilience of humanitarian supply chains and communities. For the general conclusion of the thesis, an integrative framework is presented that unifies the results identified in each article, and, therefore, explains the main aspects for the development of resilience in humanitarian supply chains of local services, in the context of natural disasters.